Extensive Scalp Angioedema following High-Dose Diphenylcyclopropenone for Alopecia Areata. Issue 1 (January 2014) - Buchanan, Rachel; Huynh, Gloria; Tanner, Jason
Objective: To describe a case of an unusual adverse drug reaction to diphenylcyclopropenone for the treatment of alopecia areata. Case summary: A 31-year-old Caucasian male presented with extensive angioedema to the head with neck involvement 10 days following treatment with diphenylcyclopropenone 2% solution in acetone topically on his scalp to treat alopecia areata. Findings on patient presentation included edema of the soft tissues (deeper dermis and subcutaneous tissue) of the head and face with mild neck involvement, acute inflammatory changes from chemical-induced irritation, scalp erythema, and serous fluid drainage from inflamed and fissured edematous scalp. Acute treatments used for control of the reaction included intravenous steroids and antihistamines during hospitalization followed by oral steroids and antihistamines for maintenance during outpatient treatment of the resolving condition. Discussion: The role of topical diphenylcyclopropenone in this case of alopecia areata is probable according to the Naranjo criteria, with a score of 8. Diphenylcyclopropenone is not approved by the US Food and Drug Administration, but it has been used by many clinicians for the treatment of alopecia areata. Diphenylcyclopropenone causes an allergic contact dermatitis in the area of hair loss. In general, diphenylcyclopropenone is applied at a high concentration of 2% once and then at lower concentrations once weekly after the sensitization dose. This patient applied the 2% concentration on multiple consecutive days. Conclusion: Frequent use of topical diphenylcyclopropenone 2% applied to the scalp may cause scalp angioedema.